Synthesis and Cytotoxic Activity on Human Cancer Cells of Novel Isoquinolinequinone–Amino Acid Derivatives - Valderrama, Jaime A. (Molecules, 2016)
A variety of aminoisoquinoline-5,8-quinones bearing α-amino acids moieties were synthesized from 3-methyl-4-methoxycarbonylisoquinoline-5,8-quinone and diverse l- and d-α-amino acid methyl esters. The members of the series were evaluated for their cytotoxic activity against normal and cancer cell lines by using the (3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide) (MTT) assay. From the current investigation, structure–activity relationships demonstrate that the location and structure of the amino acid fragment plays a significant role in the cytotoxic effects. Moderate to high cytotoxic activity was observed and four members, derived from l-alanine, l-leucine, l-phenylalanine, and d-phenylalanine, were selected as promising compounds by their IC(50) ranging from 0.5 to 6.25 μM and also by their good selectivity indexes (≥2.24).